Sanguinaria mexicana (Polygonum aviculare L.). Aplicaciones y beneficios - González Begné, Mireya; Quiroz, Verónica; Reyes, Elvia; Banderas Tarabay, José Antonio; Yslas, Nicandro (CIENCIA ergo-sum; Vol. 6 Núm. 2 (1999): CIENCIA ergo-sum (julio-octubre 1999), 2017)
-